2008
DOI: 10.1177/07316844080270160101
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Novel Layered Composites of Wood Flour and PVC

Abstract: Various formulations of wood flour and rigid Poly Vinyl Chloride (PVC) composites were prepared and the effects of layering and composite composition on their physical properties were studied. Beech wood flour, PVC, Maleic Anhydride Polyethylene (MAPE), and beech veneer were used to produce the composites in a two-step conventional hot press system. Physical property tests, including equilibrium moisture content (EMC), long term water absorption and thickness swelling were carried out. The results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Water diffusion coefficients of the composite formulations were then calculated using the following formula 20. This formula has been widely used for natural fiber plastic composites2, 5, 7–9, 21 and has been found to predict water absorption rate accurately. where D is the water diffusion coefficient corrected for edge effect; m , the slope of linear portion of the water content against root time/thickness curve; M ∞ , the equilibrium moisture content, which is the value of the water absorbed such that there is no further change in the water absorption with time; h , the thickness; L , the length; and n is the width.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water diffusion coefficients of the composite formulations were then calculated using the following formula 20. This formula has been widely used for natural fiber plastic composites2, 5, 7–9, 21 and has been found to predict water absorption rate accurately. where D is the water diffusion coefficient corrected for edge effect; m , the slope of linear portion of the water content against root time/thickness curve; M ∞ , the equilibrium moisture content, which is the value of the water absorbed such that there is no further change in the water absorption with time; h , the thickness; L , the length; and n is the width.…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanism of thickness swelling is not fully known. Evaluation of the relationship between water absorption and thickness swelling can help to understand the mechanism of thickness swelling as well 7. As seen in Figure 4, for all wood flour composite formulations, thickness swelling increased nonlinearly as water absorption increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 (Shen and Springer, 1976). This formula has been widely used for natural fiber (wood flour) plastic composites (Najafi et al, 2007a;Najafi et al, 2007b;Najafi et al, 2008;Tajvidi et al, 2006;Tajvidi et al, 2008) and has been found to work well.…”
Section: Characterization Physical Testingmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] In all these studies, the main goal was limited to improving the tensile and bending properties of the composite and enhancing its resistance against water absorption. In further studies, 12-17 a combination of wood flour with glass fiber in a polymer matrix improved tensile modulus, bending strength, and panels' dimensional stability.…”
Section: Introductionmentioning
confidence: 99%